Deconstruction and prospect of mobile informatization on mental health effects of physical exercise - Liu, Yutong; Bai, Ying; Ren, Ke (Frontiers in Psychology, 2025)
This paper aims to analyze the impact of physical exercise on mental health using mobile information technology, and to provide recommendations. This paper first proposes a weighted summation method to calculate the impact on mental health, and then analyzes the results using the assessment indicators of the SCL-90 scale. The results showed that before exercise, the number of positive items on the SCL-90 scale was around 35, and mental health improved after exercise; after exercise, the SCL-90 psychological symptom scores decreased in both male and female groups, as well as in the younger and middle-aged groups, but the degree of reduction varied; the symptom improvement was particularly significant in the elderly group after exercise. Studies show that physical exercise can alleviate psychological problems in most people and improve their overall physical health.